PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS DI SEKOLAH DASAR - Amelia Lestari; Sumianto; Yusnira; Yenni Fitra Surya; Masrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted due to the low level of students’ critical thinking skills in science learning in grade IV of UPT SDN 001 Langgini. One alternative solution to address this issue is the application of the discovery learning model. The purpose of this study was to describe the improvement of students’ critical thinking skills through the implementation of the discovery learning model in grade IV of UPT SDN 001 Langgini. This study employed Classroom Action Research (CAR), which was carried out in two cycles. Each cycle consisted of two meetings and followed four stages: planning, implementation, observation, and reflection. The data were analyzed using qualitative and quantitative techniques, including individual mastery and classical mastery. The research was conducted in June 2025. The subjects of the study were 10 fourth-grade students, consisting of 2 boys and 8 girls. Data collection techniques included documentation, observation sheets of teacher and student activities, and evaluation test sheets to assess students’ critical thinking skills. The results showed that in Cycle I Meeting I, the classical mastery reached 40% with an average score of 67.5. In Cycle I Meeting II, classical mastery increased to 60% with an average score of 76.5. In Cycle II Meeting I, students’ learning outcomes improved significantly, achieving 90% classical mastery with an average score of 83. This result was maintained in Cycle II Meeting II, with classical mastery remaining at 90% and the average score increasing to 88. Therefore, this research is considered successful, as it achieved the predetermined success criteria, with classical mastery reaching 90% in the very critical category and meeting the minimum mastery criterion of 75%. The findings indicate that the discovery learning model is effective in improving students’ critical thinking skills. Keywords: Skills, Critical Thinking, Discovery Learning Model